Performance Measurement and Management Practices in the Saudi Arabian Public Sector - Abdullah, Nur Anisah; Lawrie, Gavin; Alkahtani, Moshobab (2012)
This paper presents the initial findings from currently ongoing survey of performance measurement and management practice in the Saudi Arabian public sector. The survey forms part of a wider experimental study seeking to test and validate a proposed standardised approach to the measurement of some aspects of the performance of public agencies: the aim of the wider study being to provide a methodological foundation for the broad scale monitoring of agency productivity within the Saudi Arabian public sector. The intention of the monitoring being to recognise and / or encourage improvements in agency productivity and effectiveness.